Amorphous Solid Dispersions and the Contribution of Nanoparticles to In Vitro Dissolution and In Vivo Testing: Niclosamide as a Case Study - Miguel O. Jara; Zachary N. Warnken; Robert O. Williams (MDPI AG, 2021)
We developed an amorphous solid dispersion (ASD) of the poorly water-soluble molecule niclosamide that achieved a more than two-fold increase in bioavailability. Notably, this niclosamide ASD formulation increased the apparent drug solubility about 60-fold relative to the crystalline material due to the generation of nanoparticles. Niclosamide is a weakly acidic drug, Biopharmaceutics Classification System (BCS) class II, and a poor glass former with low bioavailability in vivo. Hot-melt extrusion is a high-throughput manufacturing method commonly used in the development of ASDs for increasing the apparent solubility and bioavailability of poorly water-soluble compounds. We utilized the polymer poly(1-vinylpyrrolidone-co-vinyl acetate) (PVP-VA) to manufacture niclosamide ASDs by extrusion. Samples were analyzed based on their microscopic and macroscopic behavior and their intermolecular interactions, using differential scanning calorimetry (DSC), X-ray diffraction (XRD), nuclear magnetic resonance (NMR), Fourier-transform infrared (FTIR), and dynamic light scattering (DLS). The niclosamide ASD generated nanoparticles with a mean particle size of about 100 nm in FaSSIF media. In a side-by-side diffusion test, these nanoparticles produced a four-fold increase in niclosamide diffusion. We successfully manufactured amorphous extrudates of the poor glass former niclosamide that showed remarkable in vitro dissolution and diffusion performance. These in vitro tests were translated to a rat model that also showed an increase in oral bioavailability.